Rediscovery of 1921. Coto- Almirante - Quesada, Juan Rafael (2022)
The publication of the prolegomena of the investigation of the 1921 war between Costa Rica and Panama invites the reader  to inquire about this scarcely known war. These prolegomena introduce the reader to a series of primary sources that shine a different light on the conflict. It defines it not only as a violent conflict, but as a forgotten war, with fallen soldiers, forgotten by the government. For example, it mentions that it wasn’t until 1961, that a plaque and a monument to commemorate their feat was unveiled at Morazan Park in San José.  These prolegomena analyzes the 1921 war from different perspectives including the literature that developed in the area as a result of the event. It also examines the role of the border and the southern area of the country. Press articles are abundant and take a privileged part in the investigation. In conclusion, these brief reviews of the writings of the war reveal the infinity of documents examined for a bigger investigation project, which goal is to recognize the significance of these events which haven’t been addressed with the importance they deserve.